Evaluation of nutrient content and in-vitro gas production of complete feed based on corn stover (Zea mays) supplemented by mimosa powder and myristic acid - Muchamad Muchlas; Siti Chuzaemi; Mashudi Mashudi (Universitas Sebelas Maret, 2020)
Objective: The purpose of this research was to evaluate the effect supplementation of mimosa powder as a source of condensed tannins and a single fatty acid, myristic acid, in a complete feed based on corn stover (Zea mays) using the in-vitro gas production method. This research has been carried out at the Animal Nutrition and Food Laboratory, Faculty of Animal Husbandry, Brawijaya University. The time of the research was conducted in August until December 2019.Methods: The experimental design used randomized complete block design by ANOVA consisting four treatments and three replications which were P1= a complete feed based on corn stover (Zea mays) as control Diet (CD) (40% corn stover + 60 % concentrate), P2= (CD) + Mimosa Powder(MP) 1.5 %/kg DM + myristic acid (MA)2% /kg DM, P3= CD + MP 1.5 % /kg DM + MA 3% /kg DM, and P4= CD + MP 1.5 %/kg DM + MA 4 %/kg DM.Results: The results showed that the treatments affected total gas production (p<0.01). The highest value for total gas production was found in P1 (86.67 ml/500 mg DM) and the lowest was found in P3 (73.30 ml/500 mg DM). The results showed that gas production decreased concurrently with the increase of MA level. In vitro methane gas and carbon dioxide production was showed different (p<0.05) from the control treatment. The lowest concentration of methane production was in P4 (82863.07 ppm) and the highest concentration was in treatment P1 86530.89 ppm. The highest total carbon dioxide content was P1 (436711.57 ppm) and the lowest concentration was P3 (350287.72 ppm).Conclusions: The results of the research concluded that the addition of mimosa powder and 3 different levels of myristic acid in a complete feed based on corn stover can increase the nutritional value of a complete feed and reduce the production of methane gas.